El mediador insomne: Fredi Guthmann en Asia y las Islas del Pacífico (El Hilo de la Fabula, 2019)
This paper attempts to capture the life and works legacy of Fredi Ghutmann (1911–1995), notorious Franco–Argentine poet and adventurer who traveled widely and lived in various countries of Asia and the Pacific. His intellectual nonconformism and rebellious character, led him to developa fragmented, suggestive and lucid work, which left deep marks on great writers of the twentieth century, as Benjamin Fondane or Julio Cortazar. We examine here the scattered evidence of his posthumous work contained in four books with poems, letters and photo albums.
Keywords: Fredi Ghutmann; legacy; mediator; Orient